(untitled) (International Journal of Automation and Smart Technology, 2025)
Most people associate the concept of automation with conventional robots, such as humanoid robots and the mechanical arms used in industry. However, the concept of intelligent automation has gradually evolved and taken shape over the past few years. auSMT editors have therefore specially interviewed Dr. Lai-Sheng Chen, deputy director of the Mechanical and Systems Research Laboratories, Industrial Technology Research Institute (ITRI MSL), to share his international viewpoints to intelligent automation, and provide academic researchers with new research directions. His point of view will give readers a brand-new perspective on automation.